“So good women are the obedient…” : an in-depth analysis of selected translated Quranic verses regarding women - Sharahil, Fatma Ahmed Abdallah Ba; Tan, Debbita Ai Lin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Examining the translations of Quranic verses related to women might clarify claims that Islam oppresses women, and in which women are abused and deprived of their rights. Furthermore, the outcomes of a translation process can be influenced by different choices, which may lead to loss or gain in meaning. In this study, five of the more known and comprehensive verses pertaining to women were selected via purposive sampling and their English renditions by two translators were analyzed using a model of translation criticism proposed by Farahzad (2012). The translations by M.M. Pickthall (1930) and S.M. Sarwar (2011) formed part of the corpus. Ibn Kathir’s (2003) exegesis was utilized to determine each verse’s meaning/interpretation. The renditions were compared against the original (Arabic) versions, and analyzed at the textual level subsumed under the dimension of translational choices. The analysis also took into account the translators’ different backgrounds; instances of disparity are apparent in terms of translational choices and a portion may be inferred to have occurred because of the translators’ backgrounds. However, these instances are minimal. Overall, the findings indicate disparities in choice of lexis, grammar, and translation strategies. Literal translation was also found to be a dominant strategy, in addition to inaccuracies in meaning conveyance. To date, there is no available translational research similar to the present study in terms of corpus and design. This study and its findings are of relevance not only to religious units, but also to translators, educators and scholars engaged in language and translational research.